1975
DOI: 10.1128/aem.30.3.369-373.1975
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Wine Composition on the Heat Resistance of Potential Spoilage Organisms

Abstract: Pasteurization studies were conducted on 29 yeasts and five lactic acid bacteria. In general the yeasts were more heat resistant in wine than were the bacteria. The one exception was a strain ofLactobacillus fructivorans that gave an average D-value of 1.7 min at 60 C. Alcohol was the wine constituent that had the greatest effect on resistance; D-values for all test species were inversely related to the ethanol concentration. The response of organisms to other factors such as pH, sugar, and sulfur dioxide vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…The order of effectiveness for both ascospore and vegetative cell heat inactivation was orange Ͼ cranberry Ͼ apple Ͼ grape Ͼ pineapple. The similar pH of the juices and the small reported influence of pH on the heat resistance of yeast (Beuchat, 1981;Splittstoesser et al, 1975) seemed to indicate that these differences in heat resistance were related to the fruit juice composition.…”
Section: Resultsmentioning
confidence: 85%
“…The order of effectiveness for both ascospore and vegetative cell heat inactivation was orange Ͼ cranberry Ͼ apple Ͼ grape Ͼ pineapple. The similar pH of the juices and the small reported influence of pH on the heat resistance of yeast (Beuchat, 1981;Splittstoesser et al, 1975) seemed to indicate that these differences in heat resistance were related to the fruit juice composition.…”
Section: Resultsmentioning
confidence: 85%
“…This level of ethanol tolerance is rarely observed with microorganisms living in ordinary environments. On the other hand, L. fructivorans, in addition to its high tolerance to ethanol (20-21% (v/v)), is relatively heat-tolerant and therefore survives suboptimal pasteurization processes 98,131 . As for wine, L. fructivorans and L. hilgardii have been reported as spoilage LAB 9,138 .…”
Section: Part 1: Beer Spoilage Lab -Their Emergence and Evolution I mentioning
confidence: 99%
“…Related studies on wine pasteurization have also found that relatively low levels of pasteurization are suitable for reducing yeast populations. In a study by Splittstoesser et al (1975), most yeast species had D-values at 49 °C of 0.6 min or below in grape wine containing 12.1% ethanol. When calculated in terms of PUs, this pasteurization treatment is equivalent to 0.016 PUs.…”
Section: Parameter Part I Part Iimentioning
confidence: 97%
“…The chemistry of a particular cider may also contribute to the pasteurization procedure followed. Previous studies have indicated that ethanol is an important contributor to heat processes [10,11] but factors such as pH, TA, sulfur dioxide concentrations, and others may also cause variations in pasteurization processes. Practices during commercial cider production, such as filtration or addition of chemical preservatives, might further reduce yeast populations.…”
Section: Parameter Part I Part Iimentioning
confidence: 99%